The history of courts and procedure in medieval Canon law - Hartmann, Wilfried 1942-; Pennington, Kenneth 1941- (Washington, DC The Catholic University of America Press, 2016)
By the end of the thirteenth century, court procedure in continental Europe in secular and ecclesiastical courts shared many characteristics. As the academic jurists of the Ius commune began to excavate the norms of procedure from Justinian's great codification of law and then to expound them in the classroom and in their writings, they shaped the structure of ecclesiastical courts and secular courts as well. These essays also illuminate striking differences in the sources that we find in different parts of Europe. In northern Europe the archives are rich but do not always provide the details we need to understand a particular case. In Italy and Southern France the documentation is more detailed than in other parts of Europe but here too the historical records do not answer every question we might pose to them. In Spain, detailed documentation is strangely lacking, if not altogether absent. Iberian conciliar canons and tracts on procedure tell us much about practice in Spanish courts. As these essays demonstrate, scholars who want to peer into the medieval courtroom, must also read letters, papal decretals, chronicles, conciliar canons, and consilia to provide a nuanced and complete picture of what happened in medieval trials. This volume will give sophisticated guidance to all readers with an interest in European law and courts
Introduction to the courts / Kenneth Pennington -- The siting of law between sacred and profane in medieval Italy and Germany / Barbara Deimling -- The practice of Canon law / James A. Brundage -- Procedure in the courts of the IUS commune / Charles Donahue, Jr -- The jurisprudence of procedure / Kenneth Pennington -- The Roman curia / Brigide Schwarz -- Judges delegate / Charles Duggan -- The ecclesiastical courts : introduction / Charles Donahue -- France and adjoining areas / Charles Donahue and Sara McDougall -- Local ecclesiastical courts in England / R.H. Helmholz -- Ecclesiastical procedure in medieval Spain / Antonio Garcia y Garcia -- Ecclesiastical procedure in Eastern Central Europe / Peter Cardinal Erd?.
Includes bibliographical references and index
Keywords: Catholic Church -- Rota Romana -- History; Catholic Church - Rota Romana; Ecclesiastical Courts -- History; Justice, Administration of (Canon law) -- History; Procedure (Canon law) -- History; Canon Law -- History; Tribunaux ecclésiastiques - Histoire; Justice - Administration (Droit canonique) - Histoire; Procédure (Droit canonique) - Histoire; Droit canonique - Histoire; RELIGION / Christian Theology / Ecclesiology; RELIGION / Christian Church / Canon & Ecclesiastical Law; Canon Law; Ecclesiastical Courts; Justice, Administration of (Canon law); Procedure (Canon law); History; Aufsatzsammlung